The Effect of Conflict Management Styles on Stakeholders’ Relationship Quality with the Moderating Role of Task Conflict - Ifrah Laiq (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
The main purpose of the study is to examine the effects of conflict management styles (integrating, obliging, compromising, dominating, avoiding) on stakeholders’ relationship quality in construction projects of Pakistan. The study further examined the moderating role of task conflict as the gap identified the little research on the effectiveness of conflict handling styles in a high or low level of conflict. The study has considerable importance from a practical aspect as it guides the project managers to know the effective way of dealing with conflict in different situations and when arises. For this quantitative study, a survey was conducted in July 2021 in construction companies of Pakistan through paper and web-based questionnaires. The target sample for the study was 400 including both male and female internal stakeholders. The results of this study demonstrate the positive effects of two approaches integrating and obliging in most situations and the negative effect of other styles dominating and avoiding also supported. Whereas the study doesn’t support the positive effect of compromising as it could involve losing the benefits and interests of stakeholders in a project. Furthermore, the study has confirmed the moderating effect of task conflict on the relationship between integrating and stakeholders’ relationship quality and avoiding and stakeholders’ relationship quality. The study is limited by its cross-sectional data and the data was collected only from internal stakeholders so the feedback of the study was restricted to only one party of a project. For further research on a similar line, it has been recommended that future studies should be conducted by incorporating the longitudinal research design and the responses should also be recorded by involving both internal and external stakeholders of the project. Also, the study recommended examining the effect of different combinations of conflict management styles on relationship quality.